From Memorization to Meaning Making: Deep Learning as a Pathway to Higher Order Thinking in Islamic Religious Education - Mukmin Mukmin; Muhammad Nasir; Shafa Shafa (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
instruction in Islamic Religious Education (IRE) and analyze its impact on students’ higher-order thinking skills at SMA Negeri 1 Tenggarong. The background of this research arises from the prevalence of surface learning practices in IRE, which emphasize rote memorization and fail to foster 21st-century skills such as critical, analytical, evaluative, and creative thinking. The study employed a qualitative approach with a case study design. The participants consisted of IRE teachers, students, parents, and school administrators selected through purposive sampling. Data were collected through observation, in-depth interviews, higher order thinking skills (HOTS) tests, and documentation, then analyzed using Miles and Huberman’s interactive model involving data reduction, display, and conclusion drawing. The findings revealed a transformation from memorization-based learning toward deeper understanding through case analysis, behavioral evaluation, and authentic projects such as Islamic-themed videos and podcasts. Students demonstrated improvement in higher-order thinking by linking Qur’anic verses and Hadith to contemporary issues like digital ethics and intolerance. This study concludes that deep learning is an effective instructional model to enhance students’ cognitive, affective, and psychomotor competencies and can serve as a strategic approach for realizing the “Pancasila Student Profile” in the context of 21st-century Islamic education.